Penerapan Forward Chaining Dengan Z-Score Untuk Monitoring Gizi Balita - Septiani, Noer Azni; Ramadhan, Fadhillah Luthfi (LPPM STIKOM Tunas Bangsa, 2024)
The development of toddlers is a critical phase in human life that requires careful attention and monitoring. One of the efforts that can be done for parents is to monitor the health condition of mothers and babies regularly and to the Integrated Service Post or commonly known as Posyandu. Parents who have difficulty monitoring and understanding their child's development appropriately. At the age of toddlers, children experience rapid physical and cognitive growth, forming the basis for their future health and well-being. Posyandu Ekadyasa Tangerang, posyandu cadres admitted that they often get obstacles in searching for data, recording data, to mistakes in entering data that is done manually, with manual data recording causes difficulties if books or note paper are damaged or lost, so that cadres experience difficulties in checking data again. This data collection is needed to understand babies who are under the Anthropometric standard of nutritional assessment. The calculation uses anthropometry and Zscore calculations, observing the nutritional tolerance part in toddlers, from the above problems the author aims to develop a monitoring system that can provide appropriate advice and recommendations to parents or health workers based on the results of nutritional monitoring of toddlers by using the application of the forwad chaning method with the development method used is XP